PENGELOLAAN BUMDES SUMBER ABADI DI DESA NGABAN KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO - Halimatus Laili Nur Qomariyah; Ilmi Usrotin Choiriyah (LPPM Universitas Abdurrab, 2026)
This research aims to analyse the management of the Sumber Abadi Village-Owned Enterprise (BUMDes) in Ngaban Village, Tanggulangin District, Sidoarjo Regency. This study is based on the gap between the role of BUMDes as a driver of the village economy with various implementation obstacles that still often appear in the field. This research uses a qualitative approach with data collection techniques through interviews, observations, and documentation. The research results show that the management of BUMDes Sumber Abadi is still facing several major problems, including limited human resources, lack of innovation in the development of business units, and high dependence on village funds. This condition has an impact on low financial independence and less than optimal institutional performance of BUMDes. This research gives theoretical implications about the importance of strengthening the capacity of managers in the governance of BUMDes. Practically, the research emphasises the need for business unit diversification, improvement of HR competence, and optimisation of cooperation with third parties to increase business sustainability.